The Effect Of Esg Disclosure And Financial Performance On Firm Value - Santoso, Iqbal Pangestu (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the Effect of ESG Disclosure and Financial Performance on Firm Value (Companies in the Food and Beverage Sub-sector listed on the Indonesia Stock Exchange). This research covers a four-year period, specifically from 2020 to 2023. The research methodology employed is a quantitative method using panel data and secondary data obtained from the Indonesia Stock Exchange website and company websites. The sampling technique used is purposive sampling with data from 2020 to 2023. Data analysis is conducted through multiple linear regression by performing descriptive statistical tests, classical assumption tests (multicollinearity and heteroscedasticity tests), and hypothesis testing using t-statistics and f-statistics to assess the significance of effects collectively at a 5% significance level. The results of this study indicate that, partially, the variables ESG Disclosure and Return On Assets have a positive and significant effect on Firm Value, while the Return On Equity variable has a negative and significant effect on Firm Value. The Net Profit Margin and Leverage variables, however, show no significant effect on Firm Value. Meanwhile, simultaneously, the independent variables ESG Disclosure, Net Profit Margin, Return On Assets, Return On Equity, and Leverage have a significant effect on Firm Value. The coefficient of determination from this study is 96.1191%, indicating that variations in the independent variables ESG Disclosure, Net Profit Margin, Return On Assets, Return On Equity, and Leverage can explain 96.1191% of the changes in the Firm Value variable, while the remaining 3.8809% is influenced by other independent variables.